Symbolic Violence Towards Precarious Worker of E-Commerce Company of Transportation Services - Firdaus, Risya Zahrotul; Agustin, Sari Monik (UI Scholars Hub, 2019)
This research is motivated by the lack of research on the symbolic violence that raised the precarious workers as their subjects. Most studies on symbolic violence that occur in organizations are focused on hierarchical organizations, where obviously dominant and dominated positions are already visible. The phenomenon of precarious workers in Indonesia is widely discussed in the various field of academic, especially the field of law that discusses the unavailability of laws governing online transportation business. The absence of such laws, then becomes a chance for online transportation companies to gain profit by abusing the interests of others (in this case, their partners). Precarious workers in the online transportation business are recruited with a partnership agreement, which should place their position equal to the e-commerce transportation company. But in reality, precarious workers are dominated by e-commerce transportation companies. This study aims to determine the symbolic violence received by precarious workers in the online transport business. This study used the concept of symbolic violence from Pierre Bourdieu, where symbolic violence is closely related to doxa, habitus, capital and arena. This research uses the paradigm of critical constructivism and is descriptive qualitative research. This study also used in-depth interviews of 4 informants as the data collection techniques. The results of this study indicate the occurrence of symbolic violence towards precarious worker in the cooperative relations (partnership agreement) with the e-commerce company in the form of bonus gains policy, tariff policy, and punishment policy. This study has identified the doxa, habitus, capital and arena that encourage symbolic violence towards precarious workers. This study also found that there are two types of precariat workers and differing acceptance of symbolic violence. The differences are influenced by factors such as gender and the motive of the precarious workers when they join the e-commerce company.